Aquascape Media for Learning Ecosystem Materials in Elementary Schools - Wisnu Cahyo Laksono; Sumardi; Ahmad Muhibbin; Yenny Prastiwi; Laili Etika Rahmawati (International Journal of Elementary Education, 2022)
A Nowadays teacher has not been able to accommodate the media needs by the cognitive development of students. Good learning media that adapted to the characteristics of students is needed. Aquascape media is learning media that accordance with the characteristics of students at the stage of concrete operational cognitive development. The purpose of this study was to development of aquascape media in learning ecosystem materials. This research approach uses research and development which specifically describes the trial phase of this media development. The stage that will be the focus of the research is the aquascape media test on the media and material aspects. The questionnaire technique was used to collect data on the feasibility of media and aquascape materials. Analysis of the media and material expert questionnaire data was carried out using quantitative techniques. The results showed that the aquascape media that was developed was based on the assessment of two media experts from academics and practitioners, and obtained an average percentage score of 91.06%. The results of the assessment of material experts from academics and practitioners get an average percentage score of 95.53%. The appropriate test results from media and material experts are in the range of 81% to 100%, which means that the aquascape media is feasible and ready to be applied without the need for revision and the results of the effectiveness test showed that the pretest and posttest on the main field test showed that Aquascape media was effectively used in learning.